2016
DOI: 10.1016/j.eurpsy.2016.01.1512
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, perceived social support and quality of life in Malaysian breast cancer patients: A 1-year prospective study

Abstract: Background: Depression and anxiety are common psychiatric morbidity among breast cancer patient. There is a lack of study examining the correlation between depression, anxiety and quality of life (QoL) with perceived social support (PSS) among breast cancer patients. This study aims to study the level of depression, anxiety, QoL and PSS among Malaysian breast cancer women over a period of 12 months and their associations at baseline, 6 and 12 months. Methods: It is a 12 months prospective cohort study. Two hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
42
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 20 publications
9
42
1
7
Order By: Relevance
“…26 This is also supported by findings from a previous study in Malaysia, whereby the presence of social support in the lowincome group was associated with increased HRQoL. 27 In a pooled analysis of 25 EORTC randomized controlled trials that included data from 6024 cancer patients, age was found to be a significant predictor of HRQoL. 28 Besides managing the side effects from their cancer and treatment, older cancer patients also face additional challenges in dealing with age-related health problems.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…26 This is also supported by findings from a previous study in Malaysia, whereby the presence of social support in the lowincome group was associated with increased HRQoL. 27 In a pooled analysis of 25 EORTC randomized controlled trials that included data from 6024 cancer patients, age was found to be a significant predictor of HRQoL. 28 Besides managing the side effects from their cancer and treatment, older cancer patients also face additional challenges in dealing with age-related health problems.…”
Section: Resultssupporting
confidence: 56%
“…Notably, previous studies have shown that ethnicity is an independent determinant of HRQoL as it tends to serve as a proxy of cultural health beliefs, social support, spirituality, and socioeconomic status. 27,30 Unfortunately, we were unable to adjust for the ethnic differences among participants as the data were not collected within the main framework of the ACTION study. Furthermore, cancer care subsidy in MOH hospitals are higher than in the public academic hospitals, making it possible for patients in MOH to experience less financial concerns than their counterparts seeking care in the academic and private hospitals, ultimately leading to a better sense of well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, social QoL in our study was higher than levels found in the general population. This could be because cancer patients often receive high level of social support from family and friends particular during diagnosis and treatment 41. Our findings about reduced physical functioning compared with Sherman et al's study,14 which examined MM patients, on average 3 months after diagnosis, albeit using a different QoL measure-the SF 12.…”
mentioning
confidence: 51%
“…Preliminary testing for the English-language HADS yielded a Cronbach a of 0.91. 20 The Malay version of the HADS has been used in previous large cohort studies in Malaysian patients with cancer 21 and has demonstrated excellent internal consistency with Cronbach a values of 0.88 for the anxiety subscale and 0.79 for the depression subscale. 22 The anxiety and depression subscales on the HADS are 7-item subscales scored on a 4-point Likert scale (from 0 to 3; with higher scores indicate more distress), yielding maximum subscale scores of 21 for anxiety and depression, respectively, and a maximum total score of 42.…”
Section: Psychological Distressmentioning
confidence: 99%